Regnase-1 in cDC1 controls T cell priming and shapes the dynamics of experimental autoimmune encephalomyelitis - Rong, Xingyu; Wang, Hai; Muraoka, Shintaro; Uehata, Takuya; Yoshinaga, Masanori; Kaisho, Tsuneyasu; Takeuchi, Osamu (Frontiers in Immunology, 2026)
IntroductionMultiple sclerosis is a chronic inflammatory demyelinating disease of the central nervous system (CNS), in which various immune cells contribute to disease progression, yet the role of dendritic cells (DCs) remains incompletely understood. The RNA-binding protein Regnase-1 plays an important role in regulating immune cell function, but its function in DCs, particularly conventional type 1 DCs (cDC1), has not been defined.MethodsWe investigated the role of Regnase-1 in cDC1 and its impact on experimental autoimmune encephalomyelitis (EAE) on Regnase-1fl/+ Xcr1-Cre+ and control mice.ResultsReduced Regnase-1 expression in cDC1 enhanced pro-inflammatory gene expression and increased their capacity to activate T cells. In the EAE model, Regnase-1fl/+ Xcr1-Cre+ mice displayed accelerated inflammatory progression during the acute phase, accompanied by increased infiltration of Th1 cells and activated CD8+ T cells in the CNS. Subsequently, Regnase-1fl/+ Xcr1-Cre+ mice showed accelerated recovery, together with increased frequencies of central memory CD8+ T (Tcm) cells.DiscussionOur study reveals the complex role for cDC1 with reduced Regnase-1 expression in inflammatory regulation, exacerbating inflammatory responses during the acute phase, while facilitate recovery. This dual role highlights Regnase-1 in cDC1 as a critical regulator that balances inflammation and immune memory.